Digital Clock and Recall: a digital, process-driven evolution of the Mini-Cog - Gomes-Osman, Joyce; Borson, Soo; Toro-Serey, Claudio; Banks, Russell; Ciesla, Marissa; Jannati, Ali; Morrow, W. Isaiah; Swenson, Rod; Libon, David; Bates, David; Showalter, John; Tobyne, Sean; et al. (Frontiers in Human Neuroscience, 2024)
Introduction: Alzheimer's disease and related dementias (ADRD) represent a substantial global public health challenge with multifaceted impacts on individuals, families, and healthcare systems. Brief cognitive screening tools such as the Mini-Cog© can help improve recognition of ADRD in clinical practice, but widespread adoption continues to lag. We compared the Digital Clock and Recall (DCR), a next-generation process-driven adaptation of the Mini-Cog, with the original paper-and-pencil version in a well-characterized clinical trial sample. Methods: DCR was administered to 828 participants in the Bio-Hermes-001 clinical trial (age median ± SD=72 ± 6.7, IQR = 11; 58% female) independently classified as cognitively unimpaired (n=364) or as having mild cognitive impairment (MCI, n=274) or dementia likely due to AD (DLAD, n=190). MCI and DLAD cohorts were combined into a single impaired group for analysis. Two experienced neuropsychologists rated verbal recall accuracy and digitally drawn clocks using the original Mini-Cog scoring rules.Inter-rater reliability of Mini-Cog scores was computed for a subset of the data (n=508) and concordance between Mini-Cog rule-based and DCR scoring was calculated.Results: Inter-rater reliability of Mini-Cog scoring was good to excellent, but Rater 2's scores were significantly higher than Rater 1's due to variation in clock scores (p<0.0001). Mini-Cog and DCR scores were significantly correlated (τB=0.71, p<0.0001). However, using a mini-cog cut score of 4, the DCR identified more cases of cognitive impairment (n=47; χ 2 =13.26, p<0.0005) and Mini-Cog missed significantly more cases of cognitive impairment (n=87). In addition, the DCR correctly classified significantly more cognitively impaired cases missed by the Mini-Cog (n=44) than vice versa (n=4; χ 2 =21.69, p<0.0001). Discussion: Our findings demonstrate higher sensitivity of the DCR, an automated, process-driven, and process-based digital adaptation of the Mini-Cog. Digital metrics capture clock drawing dynamics and increase detection of diagnosed cognitive impairment in a clinical trial cohort of older individuals.